Pengaruh Likuiditas, Risiko Bisnis, Pertumbuhan Penjualan terhadap Struktur Modal (Studi Empiris Pada Perusahaan Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Siti Nur Sari; Triyani Budyastuti (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2022)
The purpose of this research is to find effect of Liquidity, Business Risk and SalesGrowth on Capital Structure in Agricultural Sector Companies Listed on the Indonesia Stock Exchange (BEI) 2015-2019 period. The sampling technique using purposive sampling. And the data of the research is secondary data consist of 17 companies. The analysis of the study using the SPSS 25 with multiple liniear regression analysis techniques. The result of the research shows that: 1) Based on partial research result, it be can amount of liquidity has significant effect on capital structure. 2) The business risk has no significant effect on capital structure. 3) The sales growth has no significant effect on capital structure.